2020
DOI: 10.3892/ol.2020.11851
|View full text |Cite
|
Sign up to set email alerts
|

SMAD‑6, ‑7 and ‑9 are potential molecular biomarkers for the prognosis in human lung cancer

Abstract: SMADs, a family of proteins that function as signal transducers and transcriptional regulators to regulate various signaling pathways, including the transforming growth factor-β signaling pathway, are similar to the mothers against decapentaplegic family of genes and the sma gene family in Caenorhabditis elegans. SMADs generate context-dependent modulation by interacting with various sequence-specific transcription factors, such as E2F4/5, c-Fos, GATA3, YY1 and SRF, which have been found to serve a key role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…In the experimental studies on other tumor types, this paradoxical effect of TGFβ has been shown to be mediated through , for example, SMAD3. 61 On the other hand, our analyses based on TCGA have shown that the expression of SMAD3 mRNA was significantly negatively correlated with patient survival, which is in agreement with Niu et al 59,60 Pan et al 62 revealed that SMAD3 was a tumor suppressor for post-progression survival but an oncogene for progression-free survival. In turn, Zeng et al 63 showed that increased SMAD3 mRNA levels were not related to OS in NSCLC patients from the CBioPortal cohort.…”
Section: Discussionsupporting
confidence: 89%
“…In the experimental studies on other tumor types, this paradoxical effect of TGFβ has been shown to be mediated through , for example, SMAD3. 61 On the other hand, our analyses based on TCGA have shown that the expression of SMAD3 mRNA was significantly negatively correlated with patient survival, which is in agreement with Niu et al 59,60 Pan et al 62 revealed that SMAD3 was a tumor suppressor for post-progression survival but an oncogene for progression-free survival. In turn, Zeng et al 63 showed that increased SMAD3 mRNA levels were not related to OS in NSCLC patients from the CBioPortal cohort.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to L3 loop, a three finger-like structure in Smad seven provides additional support to bind to TGFβRI ( Miyazawa and Miyazono, 2017 ). The binding of SMAD7 and TGFβRI blocks SMAD2/3 which further prevents the formation of R-Smad/Co-Smad complex, thereby inhibiting core signalling pathway ( Pan et al, 2020 ). In a similar manner, BMP and activin membrane-bound inhibitor (BAMBI) forms BAMBI/SMAD7/TGFβRI complex which inhibits the activation of SMAD3 ( Hernandez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found an in silico interaction between hsa-miR-33a-5p and genes such as SMAD7 and ZNF281. Considering that SMAD7 acts as a transcriptional regulator and ZNF281 is a tumor-suppressive long non-coding (lnc)RNA, an increase in hsa-miR-33a-5p could lead to the downregulation of these factors and consequently to a loss of tumor suppression capability [ 57 , 58 , 59 ]. Among cells contributing to pro-tumor microenvironments, macrophages, especially of the M2 phenotype, are key players due to their ability to infiltrate the tumor microenvironment, leading to cancer progression [ 60 ].…”
Section: Discussionmentioning
confidence: 99%